ANALYSIS OF THE FACTORS DRIVING TEACHER PERFORMANCE AT SENIOR HIGH SCHOOL 1 PAMOTAN - Faradisa Aharna Putri; Susanti Dwi Ilhami (Fakultas Ekonomi, Universitas Negeri Jakarta, 2026)
Education is the basic key to innovative superior human resources. Teachers are a vital aspect that aids the educational journey and plays a direct role in boosting how well students learn. This study focuses on identifying and analyzing the effect of work environment, work discipline, work motivation, and job satisfaction on teachers’s performance at Pamotan 1 Public High School. This study uses quantitative approach. The study subjects involved 41 civil servant and PPPK teachers at SMA Negeri 1 Pamotan. The sampling strategy used was a saturated sample. To investigate the relationships between various factors, the study utilized a techique khow as multiple linear regression analysis. The results of this research show that the work atmosphere greatly effect teacher performance in a positive way. In contrast, work discipline appears to negatively effect teacher performance, but this effect is not significant. Furthermore, work motivation shows a considerable positive effect on theacher performance, while job satisfaction demonstrates a minor positive effect that is not significant. In the evaluation teaching effectiveness, 83,9% of teacher’s performance can be attributed to factors such aexplained by the variables of work environment, work discipline, work motivation, and job satisfaction. Meanwhile, the residual 16.1% is attributable to additional variables that were not detailed within the confones of this research.